P27 An evaluation of patient outcomes following percutaneous pulmonary valve implantation from a single centre. (2nd March 2016) - Myers, Daniel; Saluja, Sushant; Anderson, Simon G; McGowan, John; Schneider, Heiko; Dinsdale, Anna; Dua, Jaspal; Keavney, Bernard; Clarke, Bernard; Jenkins, Petra; Hoschtitzky, Andreas; Mahadevan, Vaikom S
Abstract : Background: Congenital right ventricular outflow tract (RVOT) dysfunction can now be treated percutaneously. There is demonstrable evidence that percutaneous pulmonary valve implantation PPVI effectively restores conduit graft viability with a consequent improvement in right ventricular pressures and exercise tolerance. Aim: This study evaluates early and late peri-procedural factors in patients with RVOT dysfunction, following PPVI using Medtronic Melody (MM) and Edwards SAPIEN (ES) valves. Methodology: This was a single-centre retrospective study of a cohort of 41 consecutive men (n = 18) and women (n = 23), mean age 26.1 ± 10.2 (±SD) years who underwent PPVI between December 2007 and November 2014. Indications for PPVI were significant homograft dysfunction in the context of previously corrected pulmonary atresia (n = 10), pulmonary stenosis (PS) or regurgitation (Ross procedure, n = 9), Transposition of Great arteries (n = 4), Tetralogy of Fallot (n = 15), and truncus arteriosus (n = 3). Patients were categorised as having pulmonary stenosis (44%), regurgitation (34%) or mixed pulmonary valve disease (22%). Invasive haemodynamic, echocardiographic, electrocardiographic (ECG) and cardiopulmonary exercise test (CPET) parameters were assessed pre and post-procedure, at 1, 6 and 12 months (and at 2 or 3 years respectively in some patients). Differences between the measurements were tested by ANOVA or with χ 2 test for proportions. Results: PPVI significantly reduced the mean baseline RVOT gradients in stenosis (45 vs18.4 mmHg); regurgitation (19.2 vs. 7.6 mmHg) and mixed disease (32.5 vs. 12mmHg). Mean right ventricular (RV) systolic pressures fell (61.6 ± 2.3 vs. 41.9 ± 2mmHg, p < 0.001) and RV diastolic pressures decreased by about 60% (14.3 ± 1.1 vs. 8.6 ± 1.4mmHg, p < 0.001). Echocardiography showed a clear improvement in pulmonary and tricuspid valve velocities (p for trend <0.01). Furthermore, there was consistent reduction in the main pulmonary artery maximum pressure gradient measured pre- procedure (Figure 1 ). No significant changes in duration of PR, QRS or QTc were apparent on follow-up ECGs. No changes were observed in CPET performance during follow-up. Discussion: Implantation of MM and ES valves in patients with pulmonary stenosis, regurgitation or mixed pulmonary diseases appear to be effective. Immediate improvement in right ventricular pressures and functional improvements demonstrated by echocardiography suggest PPVI is a worthwhile treatment option for patients with dysfunctional RVOT homografts. Multi-centre collaborations are essential to further determine long-term effects of PPVI on cardiac function, exercise tolerance and quality of life in RVOT dysfunction.